IMPLEMENTASI KECERDASAN BUATAN DALAM TUGAS KEPOLISIAN - Amalia Syauket; Ratna Indriasari; Mic Finanto Ario Bangun (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2024)
In recent years, the field of policing has undergone major changes especially in the digitization of systems and equipment used by the police as tools in crime investigation and prevention. The importance of proactive policing and prevention strategies in the digital age makes it possible to identify and prevent criminal activity before it occurs through the use of sophisticated analytical tools, intelligence roles and other digital tools. This descriptive research aims to find out how the implementation of artificial intelligence in policing in the current digitalization era? The results concluded that artificial intelligence has been implemented in various forms such as the use of artificial intelligence drones, super apps for all services and Automatic License Plate Recognition in Police tasks.